Ecuadorian Cacao Mucilage as a Novel Culture Medium Ingredient: Unveiling Its Potential for Microbial Growth and Biotechnological Applications - Tania María Guzmán-Armenteros; Luis Santiago Guerra; Jenny Ruales; Luis Ramos-Guerrero (Foods)
Cacao mucilage is typically disposed of during processing, yet its abundant content of organic compounds, polysaccharides, and nutrients renders it valuable for various applications. This scientific study investigates the suitability of cacao mucilage as an alternative culture medium for Lactiplantibacillus plantarum, Saccharomyces cerevisiae, and Aspergillus niger, aiming to provide a viable alternative to traditional media. Through a mixed-design approach, the powdered mucilage, peptone, and yeast extract ingredients were optimized using the recovery rates of each micro-organism as the response variable. The optimal formulation of the medium, consisting of 49.6% mucilage, 30% yeast extract, and 20.9% peptone, resulted in remarkable microbial recovery rates. L. plantarum achieved an outstanding recovery rate of 98.18%, while S. cerevisiae and A. niger exhibited recovery rates of 90.57% and 89.90%, respectively. Notably, these recovery rates surpassed those obtained using conventional culture mediums. Thus, cacao mucilage emerges as an effective component for formulating a natural culture medium that facilitates the growth of yeasts, lactic acid bacteria, and fungi. The yeast extract peptone mucilage (YPM) medium demonstrated enhanced growth, particularly for yeasts and lactic acid bacteria, with recovery rates exceeding 90%. Conversely, A. niger displayed a relatively lower recovery rate. These findings emphasize the potential of cacao mucilage as a valuable resource for preparing natural culture media that promotes the growth of yeasts, lactic acid bacteria, and fungi, offering promising prospects for various applications in microbiology and biotechnology.